Management of parasites of mammalian wildlife in European hedgehogs (Erinaceus europaeus). (2nd September 2022) - Wright, Ian
Abstract : Wild European hedgehogs are frequent visitors to domestic gardens and as a result, injured and debilitated animals are often found by the public and brought into veterinary surgeries for treatment and rehabilitation. One of the aspects of this process that is overlooked is the ecto and endoparasites they carry. Parasite burdens are likely to be high in diseased patients and may contribute to disease syndromes or cause primary disease in their own right. Some also have limited zoonotic potential. Veterinary nurses need to be able to help the veterinary surgeon diagnose parasitic infections in hedgehog patients and assess their significance. This article summarises the most common parasites of hedgehogs that are likely to be encountered, their diagnosis and management.